2021
DOI: 10.1021/acs.organomet.1c00464
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects on the Activity of Cp*Ir(pyridine-carboxylate) Water Oxidation Catalysts: Which Ligand Fragments Remain Coordinated to the Active Ir Centers?

Abstract: Identifying structure–property correlations for molecular water oxidation catalysts (WOCs) is strongly hampered by the complexity of the water oxidation (WO) reaction mechanism and catalyst in situ modifications. Here, the substitution effects for [Cp*Ir­(X-pic)­NO3] WOCs (pic = κ2-pyridine-2-carboxylate complexes) have been systematically explored by synthesizing several complexes differing for the nature of the X substituent on the pyridine-carboxylate ligand and testing them in WO driven by NaIO4. The activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 84 publications
(138 reference statements)
0
18
0
Order By: Relevance
“… Plot of σ-Hammett parameter versus (A) 1 H NMR chemical shift of ortho-proton on the pyridine ligands, data from Sato et al (2015) , (B) 13 C NMR chemical shift of quaternary carbon atom on the Cp, data from Rodriguez et al (2021) , (C) Redox couples Ru III /Ru II , adapt with permission from Angew. Chem.…”
Section: Substituent-modification Strategies Of Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“… Plot of σ-Hammett parameter versus (A) 1 H NMR chemical shift of ortho-proton on the pyridine ligands, data from Sato et al (2015) , (B) 13 C NMR chemical shift of quaternary carbon atom on the Cp, data from Rodriguez et al (2021) , (C) Redox couples Ru III /Ru II , adapt with permission from Angew. Chem.…”
Section: Substituent-modification Strategies Of Ligandsmentioning
confidence: 99%
“…Proceeding by a I2M pathway, an electron-withdrawing group on 1 causes destabilization of the Ru V = O species, favoring the O-O bond formation. For catalysts following WNA pathway, Rodriguez et al (2021) reported that increasing electron-withdrawing ability can facilitate the nucleophilic attack at the Ir V intermediate (a rate-determining step), therefore enhance the catalytic activity of [Cp*Ir (Xpic)NO 3 ], as indicated by the correlations between σ and the measured TOF max .…”
Section: Substituent-modification Strategies Of Ligandsmentioning
confidence: 99%
“…Nowadays, iridium­(III) complexes are highlighted as superior homogeneous catalysts for the OER. Various organic ligands were utilized ,,, to modulate activity and stabilize the iridium active centers in such compounds, but high oxidation potential of oxygen species generated along the OER causes the degradation of the ligands. ,, In this context, the reorientation to the heterogeneous Ir-based catalyst is the natural initiative. In a view of the rarity of iridium and its high cost, the maximization of metal utilization in heterogeneous catalysts is highly essential; however, typical turnover frequency (TOF) values of iridium heterogeneous OER catalysts are rather low compared to homogeneous analogues. A correct thorough adjustment of the active species size and morphology plays a pivotal role in gaining the highest activity with adequate stability.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, iridium(III) complexes are highlighted as superior homogeneous catalysts for the OER. 8−19 Various organic ligands were utilized 9,14,15,20 to modulate activity and stabilize the iridium active centers in such compounds, but high oxidation potential of oxygen species generated along the OER causes the degradation of the ligands. 11,16,21 In this context, the reorientation to the heterogeneous Ir-based catalyst is the natural initiative.…”
Section: ■ Introductionmentioning
confidence: 99%
“…7 However, latter ligands including 1,10-phenanthrolin and 2,2′-bipyridine can form only chelate rings with metal ions thus preventing the formation of high dimensional frameworks so they are also known as terminators. 8 Among O-donor ligands, pyridine-based carboxylate ligands are responsible for creating thousands of compounds known not only for their structural diversity but also for their wide variety of applications in many fields from catalysts, 9,10 luminescence, 11,12 gas adsorption 13,14 to their antiproliferative activities. 15,16 For several years, pyridine-2,6dicarboxylic acid (H 2 pydco) has received considerable attention due to the symmetric position of its carboxylate groups on each side of the pyridine ring which can form 5-membered chelate rings or bridge with neighboring metal centres.…”
Section: Introductionmentioning
confidence: 99%